An Evaluation of Cassava Pulp Feedstuff Fermented with A. oryzae, on Growth Performance, Nutrient Digestibility and Carcass Quality of Broilers - Sutisa Khempaka; Ruthairat Thongkratok; Supattra Okrathok; Wittawat Molee (The Journal of Poultry Science, 2014)
Cassava pulp contains a lot of starch, but low amounts of protein and high fiber content which limits its use as a feedstuff for broilers. However, fermentation of this pulp with Aspergillus oryzae (A. oryzae) to improve its protein content may increase its usefulness in broiler diets. Therefore, two experiments were conducted to evaluate the potential use of fermented cassava pulp (FCP) in broilers. In experiment 1 the effects of FCP on nutrient digestibility and retention were studied. FCP was prepared using cassava pulp fermented with A. oryzae and urea for 4 days. Forty-nine fifteen-day old male chickens were placed in individual cages and assigned randomly to one of 7 dietary treatment groups (one control and six FCP: 40, 80, 120, 160, 200 and 240 g/kg) for 10 days. The results indicate that nutrient digestibility and retention decreased with increasing levels of FCP (P>0.05), but the decrease was not significant at dietary levels below 160 g/kg. Experiment 2 studied the effect of FCP in broiler diets on growth performance, carcass quality and blood biochemistry. Two hundred and seventy one-day old male chicks were randomly distributed to 6 dietary groups (one control and five FCP: 40, 80, 120, 160 and 200 g/kg) for 42 days. The results show that FCP could be used as an energy source with inclusion levels up to 160 g/kg in broiler diets having no effect on growth performance, carcass composition, meat color or blood biochemistry (P>0.05). Moreover, it was found that FCP had no detrimental effects on the aspartate aminotransferase (AST) and alanine aminotransferase (ALT) of broilers (P>0.05). In conclusion, FCP can be used in broiler diets up to 160 g/kg without detrimental effects on nutrient digestibility and retention, growth performance, carcass quality or blood biochemistry.